Nano-ceftriaxone as Antibiofilm Agent - L. Abdulla, Alaa; Mizher Radhi, Muhammed; N. Khelkal, Intesar; N. Naji, Eman (International Journal of Psychosocial Rehabilitation, 2020)
Biofilms are communities of microorganisms that grow together and surrounded by an extracellular substance, which they form and prefer to adhere to living and non-living surfaces. Metals like copper, gold, silver, titanium, and zinc are known to have antibacterial and antibiofilm properties, which present alternatives to antibiotics without increasing the risk of resistance. The current study introduces the nano-form of ceftriaxone as agent has the activity to decrease biofilm production of some virulent bacterial isolates.Ninety bacterial isolates have been collected from different clinical sources. Identification was confirmed by API 20E and VITEK 2 systems. Antimicrobial susceptibility towards 16 antibiotics and minimum inhibitory concentration (MICs) of ceftriaxone before and after conversion were determined by using the two-fold broth dilution method as a complementary test to verify the pattern of resistance.MIC mean value of the nano-ceftriaxone was much less when compared with the MIC for microceftriaxone at the same concentration. Bacterial isolates under study included 12 MDR isolates have been screened for their ability to produce biofilms with and without different concentrations of micro and nanoceftriaxone ranges from (156-10000) µg/ml. The results in general showed highly variation in the biofilm formation degree as well as the reduction percentage after treatment with different concentrations of micro and nano-ceftriaxone.